Cardiovascular Complications in a Patient with COVID-19. A Case Report - Leonardo Maikel Gómez Carcassés; Yenisey Quintero Méndez; Eddy Pereira Valdés (Revista Finlay)
Sars-Cov-2, is a virus belonging to the coronaviridae family, responsible for the pandemic that has been plaguing the world since December 2019, which produces the infectious disease called COVID-19. This disease is expressed in more than half of the cases in a mild and even asymptomatic way, however, in a non-negligible number of patients it manifests itself in its most severe form, with multiple complications, and can even cause death. Along with respiratory complications, cardiovascular complications are present mainly in those patients who require admission to intensive care units, which make medical management difficult, as well as entail a worse prognosis. The case of a 70-years-old patient with a history of apparent health, who was admitted with respiratory symptoms and who, after performing the polymerase chain reaction technique with reverse transcriptase in real time, was positive for the Sars-Cov virus. -2, it was decided to transfer him to the Playa Girón Heroes Specialized Ambulatory Center, where he was hospitalized in the Intensive Care Unit for 6 days and died mainly as a result of cardiovascular complications is presented. The aim of this research is to present the case of a patient who suffered from respiratory symptoms as an initial presentation of the infection, for which a real-time polymerase chain reaction was performed, which was positive for SARS-CoV- 2.